FISCAL STIMULUS THROUGH INCOME TAX POLICY ARTICLE 21 AT THE KANWIL DIRECTORATE GENERAL OF TAXES - Rulandari, Novianita (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This Article 21 Government-borne Income Tax Incentive Policy (DTP) began to be implemented in April 2020 through PMK 23/PMK.03/2020 when the Covid 19 pandemic had spread widely in Indonesia, where many companies were shaken by the economy. Seeing the above conditions, the government carried out fiscal stimulus, one of which was through the Income Tax Incentive Policy Article 21 Borne by the Government (DTP), in order to help the economic recovery of the people affected by the Covid 19 pandemic. This study aims to analyze and evaluate how, obstacles, and efforts to overcome obstacles in the Implementation of Article 21 Government-borne Income Tax Incentive Policy (DTP) at the Tax Service Office of the South Jakarta Regional Tax Office I. This study is a qualitative research that focuses on the success implementation of the Government-borne Income Tax Incentive Article 21 (DTP) policy and the obstacles faced by collecting information through interviews with parties implementing the tax incentive policy. The results of the study found that the implementation of Article 21 Government-borne Income Tax Incentives (DTP) was in great demand by the public (the public) because it helped the community, in this case employees, maintain economic purchasing power in the midst of the Covid 19 pandemic that shook the economy in Indonesia.